Human Umbilical Cord Mesenchymal Stem Cell-Derived Exosomes Improve Ovarian Function and Proliferation of Premature Ovarian Insufficiency by Regulating the Hippo Signaling Pathway - Li, Zhongkang; Zhang, Mingle; Zheng, Jiahua; Tian, Yanpeng; Zhang, Huihui; Tan, Yi; Li, Qian; Zhang, Jingkun; Huang, Xianghua (Frontiers in Endocrinology, 2021)
Background: Premature ovarian insufficiency (POI) is associated with severe physical damage and psychological burden to women. Exosomal treatment has the potential for restoring ovarian functions and ameliorating POI. Objective: This study aimed at evaluating the therapeutic effects of human umbilical cord mesenchymal stem cell-derived exosomes (hUCMSC-Exos) on ovarian dysfunction, and to investigate the role of the Hippo pathway in exosome-mediated treatment. Methods: A POI mouse model was established by injecting cyclophosphamide after which hUCMSC-Exos were transplanted into them. Ovarian tissues and plasma of the mouse model were harvested two weeks after treatment. Ovarian morphologies and follicle numbers were assessed by hematoxylin and eosin staining. Moreover, ELISA was used to detect sex hormone levels in serum. To assess reproductive function recovery, pregnancy rate, the number of offsprings and the time to birth were recorded. Proliferation of ovarian cells in vivo was detected by immunohistochemistry and immunofluorescence staining. Moreover, we used EdU and CCK-8 assays to evaluate the proliferative ability of cultured granulosa cells. Western blotting was used to estimate the expression levels of Hippo- and proliferation-associated proteins. Results: After successful establishment of the POI mouse model, transplantation of hUCMSC-Exos was found to restore serum sex hormones levels and increased the number of ovarian follicles. Moreover, there was a significant improvement in reproductive outcomes after exosomal treatment. Furthermore, elevated ovarian proliferation was associated with regulation of the Hippo pathway. In vitro, co-culture with exosomes significantly elevated the proliferative rate of granulosa cells by regulating the Hippo pathway. However, the positive effect on proliferation observed in granulosa cells decreased when the Hippo pathway was inhibited.